Comparision of gene encoding cystatin of mungbean cultivars (Vigna radiata (L.) Wilczek) - Mau, Chu Hoang; Thanh Thanh, Nguyen Vu; Thu Trang, Nguyen Thi (Academia Journal of Biology, 2014)
Mungbean Vigna radiata (L) Wilczek is a grain legume widely grown in the world. Stresses such as hot, cold, drought and disease limit the mungbean yield. In addition, mungbean is low drought tolerance. Cystatins are protein inhibitors of cystein proteases belonging to papain family. In plants, cystatins are found to be involved in drought stress. These were isolated from Vigna unguiculata L., Glycine max L., Daucus carota L., Malus domestica. This paper reports our finding about the genes encoding cystatins isolated and assessment of drought tolerant ability from mungbean cultivars (Vigna radiata L. Wilczek) with different level of drought tolerance. Genomic DNA from two mungbean cultivars, including one with high drought tolerance (Dx208) and one with drought senstitiveness (PaEC3) are subjected for gene cloning using cystatin specific primers. Sequencing data of the two cloned cystatin gene fragments proved to be that of cystatin gene with a length of 1115 nucleotides, deviding into 2 exons and 1 intron. The PRF of coding regions of cystatin gene comprises of 267 nucleotides with encoding a polypeptide of 88 amino acids. The nucleotide sequences of the two cultivars show variations in different sites although the amino acid sequences do not differ each to other and even to that announced under the code AF454396.